Nanoscale Thermoelectrics - Wang, Xiaodong; Wang, Zhiming M. (Lecture Notes in Nanoscale Science and Technology, 2014)
For the efficient utilization of energy resources and the minimization of environmental damage, thermoelectric materials can play an important role by converting waste heat into electricity directly. Nanostructured thermoelectric materials have received much attention recently due to the potential for enhanced properties associated with size effects and quantum confinement. Nanoscale Thermoelectrics describes the theory underlying these phenomena, as well as various thermoelectric materials and nanostructures such as carbon nanotubes, SiGe nanowires, and graphene nanoribbons. Chapters written by leading scientists throughout the world are intended to create a fundamental bridge between thermoelectrics and nanotechnology, and to stimulate readers' interest in developing new types of thermoelectric materials and devices for power generation and other applications. Nanoscale Thermoelectrics is both a comprehensive introduction to the field and a guide to further research, and can be recommended for Physics, Electrical Engineering, and Materials Science departments. Offers comprehensive coverage of thermoelectric materials and nanostructures Provides the keys to understanding the theory underlying improvements in thermoelectric efficiency Describes a key enabling technology in materials science for energy applications Written by leading experts in each research area.